Pengaruh Gaya Kepemimpinan Politik Bobby Nasution terhadap Efektivitas Program Kerja sebagai Walikota Medan - Alex Prayoga; Halking (Jurnal Administrasi Politik dan Sosial, 2025)
Leadership (leadership) Leadership style is a leader's ability to influence others to achieve desired goals. In a political context, leadership style refers to how a leader influences the public to follow him or her. A leader's political leadership style can be seen through their communication with the public, their involvement in the decision-making process, and the resulting policies. Based on the description above, this study aims to determine whether Bobby Nasution's political leadership style influences the effectiveness of his or her work program as Mayor of Medan. Quantitative research methods were used in this study, including observation, questionnaire distribution, and documentation. The data obtained in the field were then analyzed using correlation tests. product moment, validity test, reliability test, and hypothesis test using the SPSS 22 application. Based on the results of the statistical test analysis that the researcher has conducted, the results of the study show a significant influence and strong correlation between the two variables, namely political leadership style on the effectiveness of the work program by obtaining tcount of 5.2679. Therefore, based on the established hypothesis, tcount 5.2679 with ttable2.002 based on the two-way test provisions with a significance level of 0.05. Thus, tcount 5,2679 ≥ ttable2.002 indicates that the hypothesis Ha is accepted and H0 is rejected, which means there is a significant influence between Political Leadership Style on the Effectiveness of Work Programs. This strong positive influence is supported by the dimensions of transformational leadership, namely charisma, motivation, intellectual stimulation, and individual attention that function as catalysts (people who accelerate change or progress) of innovation in optimizing the effectiveness of work programs by Bobby Nasution as Mayor of Medan.